BIOREMEDIATION OF WATER POLLUTANTS FROM WASTEWATER - Umar, Sani Ado; Dhakar, Ramgopal; Sa’idu, Mubarak; Sulaiman, Mustapha; Wudil, Aminu Ahmed; Shitu, Ahmad Sadi; Abdullahi, Abdullahi Rabiu; Saminu, Saminu Muhammad; Teli, Pankaj Kumar; Aliyu, Umar Adamu (FUDMA JOURNAL OF SCIENCES, 2025)
Environmental pollution caused by xenobiotics and other persistent compounds has been recognized as a significant threat to both human health and the natural environment. These pollutants, which include heavy metals, polychlorinated biphenyls, plastics, and various agrochemicals, are toxic and resistant to biodegradation. Bioremediation is an emerging and effective method for cleaning contaminated environments by removing toxic waste. This technique utilizes a range of microorganisms, both aerobic and anaerobic, to treat polluted sites. Microorganisms are crucial in bioremediation as they degrade, detoxify, and immobilize hazardous wastes and pollutants, transforming them into less toxic forms. Depending on factors like cost, pollutant type, and concentration, bioremediation can be conducted ex-situ or in situ. Consequently, the appropriate bioremediation method is selected based on these factors. This review addresses the major issue of contaminants in water, including its sources, effects on the ecosystem, remediation strategies using different biological processes that change the pollutants into less hazardous, source and types of pollutants, the principle of bioremediation, bioremediation strategies, and technologies, microorganisms in bioremediation, case study and application, monitoring, and assessment of bioremediation process, environmental impacts and sustainability, future perspectives, and challenges.